Causes of Transformation of Civil-Military Relations in Turkey - Gursoy, Yaprak (Uluslararasi Iliskiler Konseyi Dernegi, 2014)
Since 1999 Turkish civil-military relations have gone through a transformation due to several constitutional and institutional changes. The Turkish Armed Forces, which was independent of civilian oversight, had prerogatives and used veto powers over political matters, lost a significant amount of their authority in the last 15 years. The changes diminished the role of the military in providing internal security, increased the powers of the civilians in overseeing the military budget, curtailed the jurisdiction of the military courts over civilians, and finally gave more authority to civilians in senior level military promotions. Although there is still room for improvement, with these amendments, Turkish civil-military relations were put on a democratic footing.
Keywords: Turkish Armed Forces; Political Autonomy; Democratization; Military Coup; European Union; Ergenekon; Balyoz; Political Autonomy; Turkish Politics